Genetic variants in children with chronic respiratory diseases. Issue 9 (22nd July 2020) - Alsamri, Mohammed T.; Alabdouli, Amnah; Alkalbani, Alia M.; Iram, Durdana; Antony, Priya; Vijayan, Ranjit; Souid, Abdul‐Kader
Abstract: Founder mutations and autosomal recessive (AR) disorders are common in the Arabian Peninsula due to frequent consanguineous marriages. As a result, the pulmonary service at Tawam Hospital (Al Ain, UAE) routinely requests genetic testing for children with persistent (unexplained) respiratory problems. The main purpose of this report was to underscore the usefulness of these tests. Ten children with severe respiratory diseases due to complex genetic findings are described here. Forty‐one variants (six novel) were detected, averaging four per patient (range: 1‐9). Seven (17%) variants were homozygous and 34 (83%) heterozygous; some variants were known to show monoallelic expression. Using binomial probability distribution, the fetal‐risk for having AR disorder(s) as a function of the number of shared variants by a couple ranged from 0.25 (having one shared variant) to 0.9249 (having nine shared variants). In cultures where increased size of homozygous genomic segments is common, children often have multiple variants that could cause complex clinical phenotypes. Identifying pathogenic variants assists in clinical care, family counseling, and disease prevention through genetic screening.